Carbon-Related Defects in Si:C/Silicon Heterostructures Assessed by Deep-Level Transient Spectroscopy. (1st January 2017) - Simoen, E.; Dhayalan, S. K.; Hikavyy, A.; Loo, R.; Rosseel, E.; Vrielinck, H.; Lauwaert, J.
Abstract : This paper reports on a Deep-Level Transient Spectroscopy (DLTS) study of the electrically active defects in ∼100 nm Si:C stressors, formed by chemical vapor deposition on p-type Czochralski silicon substrates. In addition, the impact of a post-deposition Rapid Thermal Annealing (RTA) at 850°C on the DLT-spectra is investigated. It is shown that close to the surface at least two types of hole traps are present: one kind exhibiting slow hole capture, which may have a partial extended defect nature and a second type of hole trap behaving like a point defect. RTA increases the concentration of both hole traps and, in addition, introduces a point defect at EV + 0.35 eV in the depletion region of the silicon substrate at some distance from the Si:C epi layer. This level most likely corresponds with Ci Oi -related centers. Finally, a negative feature is found systematically for larger reverse bias pulses, which could point to a response of trap states at the Si:C/silicon hetero-interface.